MAITRISE DES NOTIONS DE PSYCHOLOGIE ET DE PEDAGOGIE CHEZ LES ELEVES DE 1ERE ANNEE DES HUMANITES PEDAGOGIQUES DE QUELQUES ECOLES DE LA VILLE DE KINDU - Alphonse, OKAMBA MUNDALA (IJRDO- Journal of Educational Research, 2022)
The main objective of this research is to evaluate the level of mastery of the learning objectives of the notions of psychology and pedagogy among the first year students of pedagogical humanities in some schools of the city of Kindu.To analyze and process the data, we calculated the arithmetic mean, the standard deviation, the coefficient of variation, the yield, the analysis of variance and the Newman Keuls Qr test.In general, the mastery of the concepts of psychology and pedagogy is unsatisfactory, mediocre.The schools surveyed do not have the same degree of learning and assimilation of the concepts of psychology and pedagogy.To improve the teaching of psychology and pedagogy, teachers can use functional didactics with active and participatory methods.